La Innovación pedagógica e inclusión social en Instituciones Educativas - Paucar Montoya, Karla Sebastiana (2025)
Disparity in the poorest communities poses representative educational challenges, highlighting the need to ensure access, contribution and success for all students. In this context, pedagogical innovation emerges as a key strategy to foster social inclusion. This systematic review, based on the PRISMA method, analyzed 35 studies published between 2019 and 2024, selected from databases such as Scopus, Web of Science and SciELO. The results show a significant relationship between innovative pedagogical practices and social inclusion. Strategies such as project-based learning, collaborative learning and the use of educational technologies stand out for effectively addressing diversity in the classroom. However, the success of these methodologies depends on adequate teacher training to generate equitable environments adapted to the needs of each student. Even so, greater institutional and governmental support is required to implement these practices in a sustainable and large-scale manner.